A method for controlled N-doping of III-V materials grown on (111)SI.
By using a method of continuously providing a constant concentration of As airflow and periodically stopping the growth of Group III-V materials in MBE, the problem of difficulty in doping control when GaAs grows on (111)Si is solved, and the growth of high-quality n-type GaAs materials is achieved.
Patent Information
- Application Number
- JP2022500861
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-09
- Filing Date
- 2020-07-07
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2040-07-07
AI Technical Summary
When growing GaAs materials, it is difficult to control their doping, especially when GaAs grows on (111)Si, unexpected doping is prone to occur, resulting in poor structural quality of the material and unstable electrical properties.
The method of growing Group III-V materials in molecular beam epitaxial method (MBE) is used to control the doping concentration and structural mass of the material by continuously providing a constant concentration of xenon hydrogen (As) gas stream during the growth process and periodically stopping the growth of Group III-V materials during the growth process, maintaining the growth temperature between 300°C and 580°C.
The controllability of doping GaAs material is achieved, the occurrence of accidental doping is reduced, the structural quality and electrical properties of the material are improved, and the compensation of n-type doping can be effectively performed to obtain high-quality n-type GaAs material.
Smart Images

Figure 0007665588000002 
Figure 0007665588000003 
Figure 0007665588000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for providing n-doped III-V material grown on (111)Si, and in particular to the method comprising steps of growing III-V material alternating with non-growth steps, wherein both the growth and non-growth steps are exposed to a constant, successive arsenic flux concentration. [Background technology]
[0002] Intrinsic semiconductor materials usually require dopants to form extrinsic semiconductors, such as n-type semiconductors, i.e., materials in which electrons are the majority carriers and holes are the minority carriers. p-type semiconductors include semiconductor materials in which holes are the majority carriers and electrons are the minority carriers. Intrinsic semiconductor material doping usually involves introducing impurity atoms into the intrinsic semiconductor. The impurity atoms are from a different element than the semiconductor material, and the impurity atoms are either donors or acceptors to the intrinsic semiconductor. Donors donate their extra valence atoms to the conduction band of the semiconductor. Acceptors accept electrons from the valence band of the semiconductor, thereby providing the intrinsic semiconductor material with excess holes, i.e., providing a p-type semiconductor. When making semiconductor devices, n-type and p-type semiconductors can be joined together to form, for example, a p-n junction.
[0003] However, it is known that semiconductor materials, when produced in a molecular beam epitaxy growth process, can show unintentional doping, for example p-type or n-type. The reason is that the structural quality of the resulting semiconductor material is imperfect (crystal defects, etc.). In such a situation, if unintentional p- or n-doping (sometimes referred to as self-doping, i.e. no added dopant agent is used) occurs in the semiconductor material, it may not be possible to use dopants to create n-type or p-type semiconductors. For example, if unintentional P-doping (or self-doping) occurs in the epitaxial growth process, it is known that it is possible to add an n-doping agent in a process called compensation doping when n-doping the material. However, this possibility, if compensation n-doping can be successful, usually depends on at least the level of p-doping present in the material.
[0004] GaAs is most commonly doped with silicon to make it n-type, but in addition it can be doped with germanium, sulfur, tellurium or tin, or beryllium, chromium or germanium to dope it n-type or p-type, respectively. A certain type of dopant can actually act as both an n-dopant and a p-dopant, depending on which position it occupies in the GaAs lattice. In the case of GaAs, this relates to all members of the carbon group, which are n-dopants if they occupy an As position and p-dopants if they occupy a Ga position. Note that Ga atoms occupying Ga positions in the GaAs lattice are referred to as Ga Ga , Ga occupying the As position is Ga As , written as ···.
[0005] The diatomic nature of GaAs makes it a very challenging material for controllable doping. Non-unit ratios between the two components Ga and As are possible, e.g., Ga As acts as a p-dopant, and As Gaacts as an n-dopant, resulting in a strong doping effect on the material. As a result, a slightly higher concentration of Ga during the formation of GaAs results in a p-type material and vice versa.
[0006] The inevitable introduction of monovacancies and dopant-vacancy complexes adds an additional layer of complexity in controlling the doping of GaAs. As vacancies (V AS ) and gallium vacancies (V Ga ) have been reported to act as p-dopants (see http: / / onlinelibrary.wiley.com / doi / 10.1002 / pssa.2210960237 / abstract), but Si Ga V Ga Dopant vacancy complexes such as Si have been found to compensate for n-doping by acting as acceptors, even though Si generally acts as the n-dopant in GaAs. Ga V Ga It has been shown that the compensation of n-doping by ZnO is strongest for high Si doping, where the Si atoms are doped with the amphoteric dopant Si As This provides an additional compensation effect by acting as a
[0007] Balancing the Ga / As ratio is particularly difficult during thin film deposition of GaAs, for example, using molecular beam epitaxy (MBE). During MBE deposition of GaAs, As is 2 and As 4 They are deposited as a mixture between As, which all have different chemisorption properties. 2 and As 4 As adheres differently to GaAs depending on the temperature and the concentration of Ga on the GaAs surface. 2 and As 4The maximum sticking coefficients of p-doped As and p-doped As have been reported to be measured at 0.75 and 0.5, respectively. When depositing GaAs using MBE, maintaining a higher vapor pressure (flux) of As than Ga is used to obtain a unity ratio between the two elements. Thus, a higher incorporation of Ga than As into the thin film results in a p-doped thin film.
[0008] [1] T.Yamamoto, M.Inai, A.Shinoda, T.Takebe, in their paper "Misorientation Dependence of Crystal Structures and Electrical Properties of Si-Doped AlAsGrown on(111)GaAs by Molecular Beam Epitaxy", Japanese Journal of Applied Physics Vol 32, p33-46 (1993), disclose how misorientation of (111)GaAs affects the doping efficiency. When the misorientation is less than 3 degrees, the efficiency of Si-doped AlAs layer on misoriented (111)GaAs is reduced, and high electrical resistance was obtained for (111) on-axis growth.
[0009] [2] T. Kawai, H. Yonezu, Y. Yamauchi, Y. Takano, and K. Pak, in their article "Initial growth mechanism of AlAs on Si(111)by molecular beam epitaxy", Physics Letters 59, p29-83 (1991), reported the use of As to grow unfaceted AlAs and GaAs on Si. 4 However, it is disclosed that As 4 The effects of ondoping were not investigated.
[0010] [3] K. Winer, M. Kawashima, and Y. Horikoshi, in their paper "Si doping efficiency in GaAs grown at low temperatures", Applied Physics Letters 58, p28-18 (1991), report on the effect of different Ga / As 4 The effect of doping using the flux ratio is disclosed. The doping is Ga / As 4 It depended on the flux ratio.
[0011] [4] A. Saletes, J. Massies, G. Neu, JP Contour, "Effect of As4 / Ga flux ratio on electrical properties of NID GaAs layers grown by MBE", Electronic Letters, Vol. 20, No. 21 (1984), discloses how the III / V flux ratio can be used to control the type and level of doping in GaAs films grown on a Si(100) surface without adding any separate doping material. This effect is denoted as non-intentional doping (NID) because by controlling the parameters of growth in a molecular beam epitaxy system, the material exhibits a tendency to variable levels of self-doping.
[0012] If a material becomes unintentionally p-doped, compensatory doping, for example with Si, does not necessarily result in an n-doped material, i.e., compensating for the unintentional p-doping. In particular, if the p-doping concentration is too high, compensatory doping may not be possible.
[0013] The present invention therefore comprises a method of epitaxial growth in an MBE (Molecular Beam Epitaxy) machine that provides control of unintentional doping, which, having regard to the object of the present invention, is to allow compensation of the n-doping of the material, resulting in an n-type material.
[0014] It is known that unintentional doping can occur when growing GaAs on silicon. Thus, there is a need for improved methods of controlled doping of III-V materials on (111)Si. In particular, there is a need for improved growth of n-type semiconductors, including at least GaAs, on (111)Si in molecular beam epitaxy growth processes. Summary of the Invention [Problem to be solved by the invention]
[0015] In particular, an object of the present invention can be viewed as providing an n-type doped semiconductor, including at least GaAs, on Si(111) with an As flux concentration that flows continuously over the Si(111) growth interface in a molecular beam epitaxy (MBE) growth process.
[0016] It is a further object of the present invention to provide an alternative to the prior art. [Means for solving the problem]
[0017] The above objects and certain other objects are therefore intended to be obtained in a first aspect of the present invention by providing a method of controllable n-doping in a molecular beam epitaxy (MBE) growth process comprising growing a III-V material on a (111)Si substrate, the nucleation layer comprising a III-Sb material, the method comprising: growing a nucleation layer, and then - directing a continuously flowing flux of arsenic at the growth interface of a (111)Si substrate; - depositing a III-V material in steps including a first step in which deposition of the III-V material is performed followed by a second step in which the deposition of the III-V material is stopped; - continuing the deposition of the III-V material according to the first and second steps while the arsenic flux is continuously flowing until the final material composition is developed; - maintaining the temperature of the epitaxial growth process in the interval between 300°C and 580°C; - The deposited material is 2×10 14 cm -3 ~3.6×10 16 cm -3 The p-type doping concentration obtained at the interval of 1.6 × 10 at room temperature. 3 cm 2 It is unintentionally doped with a mobility equal to or greater than / Vs, allowing compensatory doping with n-dopants.
[0018] Each aspect of the invention may be combined with any of the other aspects. These and other aspects of the invention will be apparent from and elucidated with reference to the embodiments described hereinafter. Although overlapping with other descriptions, various aspects of the present invention are described below. However, the present invention is not limited to the following. [1] 1. A method of providing controllable n-doping in a molecular beam epitaxy (MBE) growth process comprising growing a III-V material on a (111)Si substrate, the nucleation layer comprising a III-Sb material; - growing said nucleation layer, and then - directing a continuously flowing flux of arsenic at a growth interface of said (111) Si substrate; - depositing a III-V material in a first step followed by a second step including a period during which the deposition of the III-V material is stopped; - continuing deposition of said III-V material according to said first step and said second step while said arsenic flux is continuously flowing until a final material composition is developed; - maintaining the temperature of the epitaxial growth process in the interval between 300°C and 580°C; The deposited material is 2 x 10 14 cm -3 ~3.6×10 16 cm -3 The p-type doping concentration obtained at the interval of 1.6 × 10 at room temperature. 3 cm 2 unintentionally doped with a mobility above / Vs, allowing compensatory doping with n-doping agents; The method. [2] The method according to [1], wherein the compensating n-dopant agent is deposited simultaneously with the III-V material in the first step to result in an n-doped material. [3] The n-doping concentration is 16×10 17 cm -3 ~3.5×10 18 cm -3 The method according to [2], wherein the interval is [4] The method according to [2], wherein the n-dopant agent is from the group including silicon, sulfur, tellurium, tin, germanium, and selenium. [5] The method according to [1], wherein the arsenic flux source is provided by a solid As source with a temperature controlled cracker in the range of 600°C to 900°C. [6] The arsenic flux concentration from the source is As 4 and As 2 The method according to [4], wherein the mixture is a mixture of [7] When the cracker temperature approaches 600°C, the As 4 The concentration of As 2 As the cracker temperature approaches 900°C, the As concentration 4 The concentration of As 2 The method according to [5], wherein the concentration of [8] The arsenic flux concentration in the non-nucleation layer as measured using linear equivalent pressure (BEP) is at least 1.33322×10 -5 mbar (1.00×10 -5 T) to 3.99967 × 10 -5 mbar (3×10 -5 T) or 3.99967×10 -5 mbar (3×10 -5 The method according to claim 1, wherein the number of [9] 13. The method according to claim 1, wherein indium is one of the III-V materials deposited in an amount between 1.1 at% and 21.4 at%.
[10] 2. The method of claim 1, wherein indium is one of the III-V materials deposited in an amount according to one of the following amounts: 1.1 at%, 1.2 at%, 1.4 at%, 2.2 at%, 2.4 at%, 2.6 at%, 2.9 at%, 3.3 at%, 3.9 at%, 4.2 at%, 4.6 at%, 5.6 at%, 7.1 at%, 8.3 at%, 10.0 at%, 14.3 at%, 16.7 at%, or 21.4 at%.
[11] 13. The method of claim 1, wherein continuing the deposition of the III-V material by the first step and the second step is performed cyclically.
[12] The method described in [1], in which periods of growth arrest occur at randomized irregular intervals.
[13] The method of [1], wherein a higher As flux concentration from the As source allows for shorter growth arrest.
[14] The method according to any of
[11] to
[13] , wherein the period involving growth arrest is between 20 and 500 seconds long.
[15] The method of claim 1, wherein the nucleation layer comprises less than 20 at.% As.
[16] 13. The method of claim 1, wherein the (111)Si substrate has a miscut angle that provides steps on the (111)Si substrate surface, each step having a height equal to or less than one monolayer of molecules.
[17] The method according to [1], wherein the (111) Si substrate is an on-cut crystal.
[18] The method according to [1], wherein the epitaxial growth process can be of the digital alloy growth type.
[0019] The method of controlled n-doping of the present invention will now be described in more detail with reference to the accompanying drawings, which show examples of embodiments of the present invention and should not be interpreted as limiting other possible embodiments falling within the scope of the appended claims, and each example embodiment may be combined with other example embodiments. [Brief description of the drawings]
[0020] [Figure 1a] An example of a perfect GaAs crystal is shown below. [Figure 1b] An example of a GaAs crystal lacking arsenic atoms is shown. [Diagram 2] 1 shows a schematic diagram of an example of the growth process of the present invention. [Figure 3a] 1 shows an example of a mobility measurement in accordance with an example embodiment of the present invention. [Figure 3b] 1 shows an example of carrier density measurement in an example embodiment of the present invention. [Figure 4] 1 illustrates example process steps in an example embodiment of the present invention. [Diagram 5] An example of parameter settings for the growth process and the results obtained is given. [Figure 6a] Two-dimensional growth on a miscut (111) Si substrate surface is shown. [Figure 6b] Three-dimensional growth on a miscut-free (111) Si substrate surface. [Figure 7] 4 shows results obtained with one embodiment of the present invention. [Figure 8] Further results obtained with an example embodiment of the present invention are presented. [Figure 9] Further results obtained with an example embodiment of the present invention are presented. [Figure 10] 1 illustrates the growth of n-doped material in an MBE (Molecular Beam Epitaxy) machine according to an example embodiment of the present invention. [Figure 11a] Different examples of layer structures of example embodiments of the present invention are disclosed. [Figure 11b] Different examples of layer structures of example embodiments of the present invention are disclosed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Although the present invention has been described in relation to specific embodiments, the present invention should in no way be construed as being limited to this example. The scope of the present invention is indicated by the appended claims. In the context of the claims, the term "comprising" or "comprises" does not exclude other possible elements or steps. Also, references such as "a" or "an" should not be interpreted as excluding a plurality. The use of reference signs in the claims for elements shown in the figures should also not be interpreted as limiting the scope of the present invention. Moreover, individual features recited in different claims may in some cases be advantageously combined, and reference to these features in different claims does not exclude that a combination of features is not possible or advantageous.
[0022] FIG. 1a shows a perfect GaAs crystal containing Ga and As atoms bonded together to form a crystal structure.
[0023] Figure 1b shows a situation where an arsenic atom is missing in the crystal structure. In general, this situation is an example of unintentional p-type doping in III-V material structures. The missing arsenic atom constitutes a dangling bond from the neighboring gallium atom. These dangling bonds can act as electron donors, resulting in a local positive charge. The transfer of these charges throughout the crystal is p-type conduction.
[0024] FIG. 2 is a schematic diagram of an example of applying flux concentrations during epitaxial growth on a substrate. As known in the prior art, wires containing atoms of the respective materials with defined flux concentrations may be directed at the substrate under a given temperature. The atoms contained in each wire are then deposited on the surface of the substrate and bonded to atoms on the substrate surface. By turning each wire on and off and varying the flux concentrations, temperature and pressure as well as other parameters, several layers, which may contain different material compositions, can be added to the growth interface. In this way, it is possible to design semiconductor materials with specific properties as known in the prior art.
[0025] With respect to the description of FIG. 1b, one aspect of the present invention is the main idea of having a high flux concentration of arsenic atoms, thereby filling the arsenic vacancies in the crystal, and then using, for example, Si as an n-type dopant in the process. FIG. 2 shows the use of As as an n-type dopant material. 2 , As 4 , and the use of an arsenic flux concentration composed of a mixture of Si.
[0026] However, other factors characterizing the semiconductor material to be produced must also be taken into account: for example, excess arsenic can lead to defects in the crystals that affect the electrical properties of the semiconductor material, as known to those skilled in the art.
[0027] A particular consideration is to achieve sufficient mobility of the charges in the crystal as well as sufficient charge density in the semiconductor material. Electrical conductivity is proportional to the product of mobility and carrier concentration. For example, the same electrical conductivity can result from a small number of electrons, each with a high mobility, or a large number of electrons, each with a low mobility. In semiconductors, for example, the behavior of transistors and other devices can be very different depending on whether there is a large number of electrons with lower mobility or a small number of electrons with higher mobility.
[0028] Mobility is therefore an important parameter for semiconductor materials: usually, higher mobility leads to better device performance, provided other device characteristics or parameters are roughly the same.
[0029] Figures 3a and 3b show an example of electrical mobility measurements in an example of an unintentionally doped sample of III-V semiconductor material. Figure 3a discloses the Hall mobility which discloses the electric field dependence as a function of magnetic flux density on the mobility of charges in the material. Figure 3b shows the carrier (charge concentration) as a function of magnetic flux density. The electrical conductivity of the material is proportional to the product of the mobility and the carrier concentration as discussed above. The curves show a typical electrical conductivity of about 3.5-3.6 x 10 at room temperature. 16 cm -3 and about 1.6 to 1.7 × 10 3 cm 2 / Vs mobility is shown.
[0030] Therefore, the main principle behind the present invention is to avoid, for example, the lack of arsenic atoms in III-V semiconductor materials by increasing the arsenic atomic flux concentration when growing the III-V semiconductor materials and by using, for example, Si as an n-dopant agent when providing an n-type III-V semiconductor.
[0031] The arsenic source applied in one example of the method according to the present invention can be a solid As source equipped with a cracker. The arsenic flux concentration is 4 and As 2 It is a mixture of.
[0032] When developing and testing several examples of material samples according to the present invention, the inventors used an "Arsenic Valved Cracker Mark V 500cc" supplied by Veeco for arsenic flux generation. Using the factory recommended settings, the cracker was able to generate very low levels of As during the growth process, even at very high total arsenic flux concentrations (up to and in some cases exceeding 3E-5T) when using certain dopants (Si dopant) and substrate temperatures. 2 / As4 The flux ratio was provided, resulting in n-type doped material. 4 and As 2 The ratio of As to As can be controlled by setting the cracker temperature within the interval, for example, 600°C to 900°C. When the cracker temperature approaches 600°C, 4 The concentration of As 2 As the temperature approaches 900℃, the As concentration becomes higher than that of 4 The concentration of As 2 The concentration of
[0033] The arsenic flux ratio can be controlled as described above and depends on the arsenic source settings. Under unfavorable conditions, the resulting material is always highly p-type semiconductor (1×10 18 cm -3 (larger than 5×10) and thus makes n-type compensating doping almost impossible to achieve, as the unintentional p-type doping dominates the material. 19 cm -3 Measurements made by the inventors of n-doped material having intentional n-type doping of 1000 nm have disclosed that the material is still p-type under unfavorable conditions.
[0034] In one embodiment of the present invention, the growth process on (111)Si is 2 and As 4 The growth process involves using a mixture of different arsenic flux compositions, including but not limited to molecules. During growth, other materials are added that constitute a complete III-V material structure with n-doping. These materials include, but are not limited to, gallium, aluminum, indium, arsenic, and n-doping (silicon), with the addition of antimony being optional. In the III-V structure, silicon constitutes the dopant agent, but is interchangeable with other n-dopant agents. Growth stopping may be performed at specific intervals under arsenic flux concentrations to increase the arsenic content of the semiconductor.
[0035] Figure 4 illustrates an example of a growth process over time. The illustrated process begins with the deposition of a particular amount of a selected material, such as that disclosed in Figure 1, onto a substrate. In this example, a constant arsenic flux composition is applied during the entire growth process while deposition of the selected III-V material or material composition continues with steps having non-growth periods during which the arsenic flux concentration is still flowing. The thickness of the material increases with each step that involves growth.
[0036] In one embodiment of the present invention, periods of growth are stopped and periods of growth are allowed to alternate periodically.
[0037] In another exemplary embodiment of the present invention, periods of growth arrest occur at randomized, irregular intervals.
[0038] In another example embodiment of the present invention, increasing the As flux concentration can decrease the length of each growth arrest.
[0039] The period of growth arrest can be from 20 to 500 seconds long.
[0040] FIG. 5 shows Table 1 disclosing some examples of different parameter settings that can be used in the disclosed example of the above embodiment.
[0041] The results of III-V growth with example process parameters and growth stop intervals are shown in Table 1 of Figure 5. One example is Ga 0.95 In 0.05 As is 90cm 2 / Vs mobility of 3.5×10 18 cm -3 Another example is Ga. 0.83 In 0.17 As is 87cm 2 / Vs mobility of 2.80×10 18 cm -3 provides n-doping.
[0042] When examining the structural quality of materials processed as described above, the structural quality can possibly be improved. Referring to the prior art for (111) GaAs, the prior art suggests that the optimum growth temperature is about 670°C. This may not be possible on (111) Si, which cannot be grown above 580°C, if the nucleation layer requires high levels of Sb. The inventors have confirmed that Sb is a preferred part of the nucleation layer when growing III-V materials on (111) Si substrates.
[0043] Furthermore, annealing at too high a temperature is also not advisable if high structural quality is to be obtained, since Sb diffusion will remove Sb from the nucleation layer and create voids or defects in the III-V material.
[0044] As mentioned above, doping can induce defects in III-V structures that can act as acceptors or donors, resulting in unintended doping. Therefore, controlling the defect and / or doping levels of III-V materials is advantageous when utilizing these structures for different applications.
[0045] The use of n-type doping is important for many applications that use III-V materials grown on (111)Si, including, for example, solar cells, photodetectors, semiconductor lasers, and high electron mobility transistors (HEMTs).
[0046] The process of n-doping of III-V materials grown on (111)Si has been discussed in the prior art. For example, [2] T. Kawai on (111)Si reported As 4 have shown that facetless AlAs and GaAs can be successfully grown on silicon using As 4 The effect of on-doping of GaAs was not tested. 4 and Ga fluxes were investigated by K. Winer et al. [3], and Ga / As 4It has been shown that the efficiency of doping is dependent on the flux ratio. Yamamoto et al. [1] investigated Si-doped AlAs layers on misoriented (111) GaAs and found that when the misorientation is less than 3 degrees, the doping efficiency is reduced and the (111) on-axis growth has high electrical resistivity.
[0047] The present growth process on (111)Si is carried out using monoatomic arsenic, As 2 and As 4 Examples include using a mixture of different arsenic flux compositions, including but not limited to molecular. During growth, other materials are added that make up the complete III-V material structure with n-doping. These materials include, but are not limited to, gallium, aluminum, indium, arsenic, and n-doping (silicon), with the addition of antimony being optional. In the III-V structure, silicon constitutes the n-dopant agent, but can be exchanged for other n-dopant agents.
[0048] According to one embodiment of the present invention, growth termination, which may be regular or irregular and randomized, is introduced at specific intervals under an arsenic flux, thereby increasing the arsenic content of the semiconductor material.
[0049] The results obtained with the method of the present invention are 2×10 14 cm -3 ~3.6×10 16 cm -3 This provides unintentionally doped III-V materials on a (111)Si substrate with intrinsic p-doping at intervals of 1000 nm. This is a good starting point when providing controlled n-type doping of these materials, and n-dopant compensatory doping is possible due to the lower level of unintentional p-doping, resulting in a net n-type doping of the material. A further interesting aspect is that the n-type doping of the example material compositions grown according to the present invention may provide lower mobility, but this does not result in too high an ohmic resistance of the material.
[0050] Furthermore, annealing at too high a temperature may not provide high structural quality, as Sb diffusion will remove the Sb from the nucleation layer and create voids or defects in the III-V material. When applying Sb, the growth temperature should not exceed 580 °C.
[0051] Another aspect of growing III-V materials is that the surface of the semiconductor must be flat if the resulting semiconductor is to be used in solar cells (and also in other applications). For example, avoiding crystal facets is possible by adding indium to the III-V materials used in the growth process according to the invention. A preferred at% amount of indium is in the interval 1.1 at% to 21.4 at%. More specifically, In is selected from the group of amounts including 1.1 at%, 1.2 at%, 1.4 at%, 2.2 at%, 2.4 at%, 2.6 at%, 2.9 at%, 3.3 at%, 3.9 at%, 4.2 at%, 4.6 at%, 5.6 at%, 7.1 at%, 8.3 at%, 10.0 at%, 14.3 at%, 16.7 at% or 21.4 at%. This has been shown to reduce defects in the resulting material.
[0052] Unintentional p-doped samples after post-growth annealing are known to be caused by defects in the III-V structures acting as acceptors or donors, resulting in unintentional p-doping. Therefore, controlling the defect and / or doping levels in III-V materials is advantageous when utilizing these structures for different applications.
[0053] Another consideration for MBE growth is growing an on-cut (111)Si crystal versus a miscut crystal. In an example embodiment of the present invention, an on-cut crystal is preferred, which prevents the presence of steps on the silicon surface (see FIG. 6a). Such steps on the surface are either one monolayer or several monolayers in height. In the latter case, these steps can result in defects in the grown crystal. In the case of an on-cut crystal, the absence of steps results in 3D-like growth on the surface (see FIG. 6b). For example, if one starts growing a nucleation layer AlAsSb on top of a (111)Si surface, this appears as islands on the surface. These islands grow in size until they eventually meet, thus covering the entire surface. Once such coverage is achieved, the growth transitions to growth with a gallium-containing material. Gallium helps to reduce the 3D-like growth to achieve a flat growth surface and thus a reduction in defects. See also the planarization layers 2 and 3 disclosed in Table 2 of FIG. 11a.
[0054] Another aspect of the present invention is to avoid unintentional n-doping of the nucleation layer, so that the nucleation layer is grown separately, but the III-V material deposition should be n-doped in higher layers above the nucleation layer.
[0055] Additionally, it is within the scope of the present invention to use a technique called "digital alloy growth". This means using thinner AlInAs layers and thinner GaInAs layers, resulting in layers with higher Al content. The advantage of this approach is that the GaInAs layer can be doped without doping the AlInAs layer. See the article by Ron Kaspi et al., "Digital alloy growth in mixed As / Sb hetero-structures", Journal of Crystal Growth, Vol. 251, Issues 1-4, April 2003, pp. 515-520.
[0056] The use of n-type doping is important for many applications when using III-V materials grown directly on (111)Si. These applications include solar cells, photodetectors, semiconductor lasers and high electron mobility transistors (HEMTs). See Table 2 in Figures 11a and 11b which discloses solar cell structures including example layers according to the present invention.
[0057] FIG. 7 shows an example of the achieved results of n-type doping in one embodiment of the present invention. 0.83 In 0.17 The n-type doping concentration in As is shown. The material is grown at a temperature of 430° C. in intervals of 50 nm, with growth stopped for 294 seconds between each interval. The arsenic flux is always present (applied), the gallium and indium fluxes are only present (applied) during the growth interval. See also Table 1 in FIG. 5, which discloses the achieved mobility and n-doping concentration with different As-flux concentrations etc.
[0058] Figure 8 shows the arsenic flux as a function of n-type Ga 0.83 In 0.17 Figure 7 shows an example of the achievement of electron mobility in As. The material is grown in 50 nm thickness intervals at a temperature of 430 °C, with growth stopped for 294 seconds between each interval. The arsenic flux is always present, while the gallium and indium fluxes are only present during the growth intervals. When relatively low flux rates are present, the mobility is low due to the reduced arsenic content (as can be seen in Figure 7), and at relatively intermediate flux rates the mobility is 80-90 cm. 2 / Vs range, while at higher flux rates the mobility decreases again. Compared to Figure 7, there is no decrease in carrier concentration at higher flux rates. Thus, the decrease in mobility is due to defects associated with excess arsenic, which does not affect the carrier concentration.
[0059] There is a relationship between the duration of growth arrest and As flux concentration. The higher the As flux concentration, the shorter the duration of growth arrest can be. In this way, it is possible to manipulate the As flux concentration versus the duration of growth arrest.
[0060] In principle, there is no harm if the growth stop duration is too long. However, long epitaxial growth durations tend to introduce impurities in the MBE chamber into the material sample. This is a well-known problem, where impurities in the MBE machine itself can induce defects in the resulting material structure and thus cause unintended doping. Therefore, a shorter growth stop with a higher As flux concentration is preferred. See, for example, Figure 7.
[0061] Figure 9 shows the growth rate of n-type GaAs as a function of growth temperature. 0.83 In 0.17 The electron mobility in As is shown in Fig. 1. The material has a 2.0× -5 The samples were grown at 50 nm intervals with an arsenic flux of 1000 Å torr, stopping growth for 294 seconds between intervals. The arsenic flux is always present, while the gallium and indium fluxes are only present during the growth interval. In the example sample grown at 375 °C, proper measurements could not be made due to the high resistivity of the sample. This suggests low mobility values and / or low carrier concentrations, and is consistent with the 0 cm 2 At 430°C, the mobility is higher (87 cm 2 / Vs) and does not decrease significantly at 500°C. 0.83 In 0.17 The As carrier concentration is lower at 500 °C. The same Table 1 suggests that the reduction in carrier concentration can be countered and even increased. A reduction in the indium content when grown at these temperatures provides these effects.
[0062] FIG. 10 shows an example of a setup for producing a material sample according to the present invention.
[0063] Each material source can be a solid source or a combination of solid and gas sources. Such machines can utilize CVD (chemical vapor deposition) deposition, or MOCVD (metal organic vapor deposition) as known in the art.
[0064] Figure 11a discloses examples of material compositions for each layer of five different material samples of the solar cell design, and Figure 11b provides a brief description of each layer.
[0065] The samples have been tested with Electron Beam Induced Current (EBIC) technique, a semiconductor analysis technique performed in a Scanning Electron Microscope (SEM) or Scanning Transmission Electron Microscope (STEM), which is used to identify buried junctions or defects in semiconductors or to examine minority carrier properties as known in the art.
[0066] For example, in a solar cell, a photon of light shines across the cell, transferring energy and creating electron-hole pairs that generate an electric current. In EBIC, energetic electrons play the role of the photon, resulting in the flow of an EBIC current.
[0067] Referring to Table 2 in Figure 11a, the sample was probed with 10 keV radiation. Kanaya and Okayama developed the following equation for the penetration depth of the radiation:
[0068] The formula is as follows:
number
[0069] Using this formula for the example layer of Figure 11a, the electrons are calculated to penetrate 0.8 μm to 0.9 μm, which means that the current comes mainly from the III-V layers.
[0070] According to an example embodiment of the present invention, a method for providing controllable n-doping in a molecular beam epitaxy (MBE) growth process comprising growing a III-V material on a (111) Si substrate, the nucleation layer comprising a III-Sb material, comprises: growing a nucleation layer, and then - directing a continuously flowing flux of arsenic at the growth interface of a (111)Si substrate; - depositing a III-V material in steps including a first step in which deposition of the III-V material is performed followed by a second step in which the deposition of the III-V material is stopped; - continuing the deposition of the III-V material according to the first and second steps while the arsenic flux is continuously flowing until the final material composition is developed; - maintaining the temperature of the epitaxial growth process in the interval between 300°C and 580°C; - The deposited material is 2×10 14 cm -3 ~3.6×10 16 cm -3 The p-type doping concentration obtained at the interval of 1.6 × 10 at room temperature. 3 cm 2 It is unintentionally doped with a mobility equal to or greater than / Vs, allowing compensatory doping with n-dopants.
[0071] Additionally, a compensating n-dopant agent can be co-deposited with the III-V material in a first step to result in an n-doped material.
[0072] In addition, the n-doping concentration is 16×10 17 cm -3 ~3.5×10 18 cm -3 The interval may be .
[0073] Additionally, the n-dopant agent may be from the group including silicon, sulfur, tellurium, tin, germanium, and selenium.
[0074] Additionally, the arsenic flux source is provided by a solid As source with a temperature controlled cracker in the range of 600 °C to 900 °C.
[0075] The arsenic flux concentration from the source is 4 and As 2 It is a mixture of.
[0076] In addition, when the cracker temperature approaches 600°C, As 4 The concentration of As 2 As the cracker temperature approaches 900°C, the As concentration becomes higher than that of the 4 The concentration of As 2 The concentration of
[0077] Furthermore, the arsenic flux concentration in the non-nucleation layer measured using linear equivalent pressure (BEP) is at least 1.33322 × 10 -5 mbar (1.00×10 -5 T) to 3.99967 × 10 -5 mbar (3×10 -5 T) or 3.99967×10 -5 mbar (3×10 -5 Exceeds T).
[0078] Additionally, indium may be one of the III-V materials deposited in an amount between 1.1 at% and 21.4 at%.
[0079] Additionally, indium may be one of the III-V materials deposited in an amount according to one of the following amounts: 1.1 at%, 1.2 at%, 1.4 at%, 2.2 at%, 2.4 at%, 2.6 at%, 2.9 at%, 3.3 at%, 3.9 at%, 4.2 at%, 4.6 at%, 5.6 at%, 7.1 at%, 8.3 at%, 10.0 at%, 14.3 at%, 16.7 at%, or 21.4 at%.
[0080] Furthermore, continuing the deposition of III-V material according to the first and second steps of the method according to the invention can be performed cyclically.
[0081] Furthermore, periods of growth arrest may occur at randomized, irregular intervals.
[0082] Additionally, a higher As flux concentration from the As source may allow for shorter growth arrest.
[0083] Furthermore, the period of growth arrest may be as long as 20 to 500 seconds.
[0084] Additionally, the nucleation layer contains As in an amount less than 20 at %.
[0085] Additionally, the (111)Si substrate may have a miscut angle that provides steps on the (111)Si substrate surface, each step being equal to or less than one monolayer of molecules in height.
[0086] The (111) Si substrate may also be an on-cut crystal.
[0087] Furthermore, the epitaxial growth process can be of the digital alloy growth type.
Claims
1. 1. A method of providing controllable n-doping in a molecular beam epitaxy (MBE) growth process comprising growing a III-V material on a (111) Si substrate, the nucleation layer comprising a III-Sb material; - growing said nucleation layer, and then - directing a continuously flowing flux of arsenic at the growth interface of said (111) Si substrate; - depositing a III-V material in a first step followed by a second step including a period during which the deposition of the III-V material is stopped; - continuing the deposition of said III-V material according to said first step and said second step while said arsenic flux is continuously flowing until a final material composition is developed; - maintaining the temperature of the epitaxial growth process in the interval between 400°C and 580°C, Some or all of the deposited material is less than 2×10 14 cm -3 ~3.6 x 10 16 cm -3 The p-type doping concentration obtained at the interval of 1.6×10 at room temperature 3 cm 2 / Vs or greater to allow for compensatory doping with an n-dopant agent; or An n-dopant agent is deposited simultaneously with the III-V material in the first step to provide an n-doped material, the n-dopant agent having a concentration of at least 1.00×10 16 cm -3 and the III-V material comprises at least Ga or Al, and the deposition of the III-V material is stopped for at least 2.94 seconds per nanometer of material grown; The method.
2. The concentration of the n-dopant agent is 1.0×10 16 cm -3 ~3.5 x 10 18 cm -3 The method of claim 1 , wherein the interval is
3. The method of claim 1 , wherein the n-dopant agent is from the group including silicon, sulfur, tellurium, tin, germanium, and selenium.
4. The method of claim 1, wherein the arsenic flux source is provided by a solid As source with a temperature controlled cracker in the range of 600°C to 900°C.
5. The arsenic flux concentration from the arsenic flux source is As 4 and As 2 The method of claim 4, wherein the mixture is
6. When the cracker temperature approaches 600°C, the As 4 The concentration of As 2 When the cracker temperature approaches 900°C, the As 4 The concentration of As 2 The method of claim 5, wherein the concentration of
7. The arsenic flux concentration in the non-nucleation layer, measured using linear equivalent pressure (BEP), is at least 1.33322×10 -5 mbar to 3.99967 x 10 -5 between mbars, or 3.99967 x 10 -5 The method of claim 1, wherein the pressure is greater than 1000 bar.
8. 2. The method of claim 1, wherein indium is one of the III-V materials, and wherein the indium is deposited in an amount between 1.1 at% and 21.4 at%.
9. 2. The method of claim 1 , wherein indium is one of the III-V materials and the indium is deposited in an amount according to one of the following amounts: 1.1 at%, 1.2 at%, 1.4 at%, 2.2 at%, 2.4 at%, 2.6 at%, 2.9 at%, 3.3 at%, 3.9 at%, 4.2 at%, 4.6 at%, 5.6 at%, 7.1 at%, 8.3 at%, 10.0 at%, 14.3 at%, 16.7 at%, or 21.4 at%.
10. 2. The method of claim 1, wherein continuing the deposition of the III-V material through the first step and the second step is performed cyclically.
11. 2. The method of claim 1, wherein the periods of growth arrest occur at randomized irregular intervals.
12. The method of claim 4 , wherein increasing the As flux concentration from the solid As source decreases growth arrest duration.
13. 13. The method of any one of claims 11 to 12, wherein the period of growth arrest is between 20 and 500 seconds long.
14. The method of claim 1 , wherein the nucleation layer comprises less than 20 at % As.
15. 2. The method of claim 1, wherein the (111) Si substrate has a miscut angle that provides steps on the (111) Si substrate surface, each step having a height of no more than one monolayer of molecules.
16. The method of claim 1 , wherein the (111) Si substrate is an on-cut crystal.
17. The method of claim 1 , wherein the epitaxial growth process is of the digital alloy growth type.
Citation Information
Patent Citations
Method for growing molecular beam crystal
JP1988265898A
Method for manufacturing compound semiconductor substrate, and compound semiconductor substrate
JP2015053386A